Experimental investigation of the size effect of layered roller compacted concrete (RCC) under high-strain-rate loading. (20th March 2018) - Wang, Xiao-hua; Zhang, She-rong; Wang, Chao; Song, Ran; Shang, Chao; Fang, Xin
Highlights: Dynamic size effects on the properties of RCC material have been investigated. Statistical correlation between strain-rate and size effects on RCC is analyzed. A modified Weibull size effect law for RCC is proposed considering strain-rate effect. Abstract: The strain rate and specimen size are two main influential factors when measuring the compressive strength of concrete-like materials. Understanding the dynamic size effect of concrete is essential for better analysis and design of concrete structures. However, few systematic laboratory tests have investigated the dynamic size effect in layered roller compacted concrete (RCC) under various levels of high-strain-rate loading. In this study, three sizes of cylindrical RCC specimens with diameters of 50 mm, 75 mm and 100 mm are prepared and tested under high loading rates to directly investigate the size effects. The size dependence and strain rate sensitivity are characterized in terms of the failure pattern, dynamic compressive strength, ultimate strain, maximum strains, and toughness. The dynamic compressive strength increases with increasing specimen size under impact loading, which is opposite to the size effect under static loading. The statistical significance is further investigated in terms of the variation in the dynamic mechanical properties of the RCC material based on analysis of variance (ANOVA). A modified Weibull size effect law, which incorporates both the specimen size and strain rate, is proposed and verified to illustrate the underlying mechanism of the dynamic size effect for the RCC material under impact loading.